Multi-step wear evolution simulation method for the prediction of rail wheel wear and vehicle dynamic performance. (May 2019) - Pradhan, Smitirupa; Samantaray, AK; Bhattacharyya, R
This paper presents a complete model to estimate the effects of wheel wear on the dynamic behavior and ride comfort of a railway vehicle. A co-simulation of the vehicle dynamics modeled in ADAMS VI-Rail and wear evolution modeled in MATLAB is performed in a loop. The outputs from the vehicle dynamics simulation are used to compute the wear evolution, which in turn affects the vehicle dynamics. The local contact parameters, such as normal contact force, tangential stresses and slip, etc., and wear distribution for each cell of the contact surface are estimated with the help of Kalker's simplified theory of rolling contact and Archard's wear model, respectively. The wear distribution and smoothening of the wheel profile are obtained for a short travel distance and are then scaled up for larger travel distance. The worn wheel profile is updated in the vehicle dynamics model after every 10, 000 km of travel for further dynamic analysis and this process is repeated until either the critical dynamic performance or wheel wear limits are reached. Several new results emerge by considering both acceleration and braking on a tangent track with sinusoidal irregularities. Critical speed appears to increase initially and then decrease quickly, whereas worn wheels give better ride comfort in both lateral and vertical directions as compared to new wheels. According to the results in this work, wheels may be recommended for re-profiling or replacement much before the critical wear depth recommended in maintenance guidelines is reached.